Floristic and ethnobotanical diversity of plants used in traditional craftsmanship in the Kimvula Territory, Democratic Republic of the Congo - Lemmy Lassa; Guy Ilumbe; Jean Paul Koto-Te-Nyiwa Ngbolua; Blaise Bikandu; Monizi Mawunu; Jean Pierre Habari; Apollinaire Biloso; Da Musa Masens; Félicien Lukoki (Biology, Medicine, & Natural Product Chemistry, 2026)
The Kimvula Territory in the Democratic Republic of the Congo exhibits intensive use of forest plants in traditional craftsmanship, encompassing agricultural tools, furniture, and household artefacts. This ethnobotanical investigation (2014–2016), based on structured interviews and field observations, aimed to document and analyse indigenous knowledge related to artisanal plant use. A total of 76 species belonging to 67 genera and 32 families were recorded, with Fabaceae, Arecaceae, Marantaceae, and Rubiaceae being the most represented families. Prominent species included Elaeis guineensis, Eremospatha haullevilleana, Raphia spp., Alstonia congensis, and Ricinodendron heudelotii, with stems identified as the most commonly used plant part. Millettia laurentii exhibited the highest ethnobotanical use value, while several species showed strong consensus among respondents. Variation in species use between communities reflected both ecological availability and socio-cultural preferences. These findings highlight the pivotal role of forest biodiversity in sustaining rural livelihoods and preserving traditional craftsmanship. They further emphasize the need to integrate indigenous knowledge into conservation planning and sustainable resource management strategies across the Congo Basin.